Exploring Student Perspectives on Entrepreneurship Learning in Islamic Higher Education - Putra, Nur Astaman (Journal of Economic Education and Entrepreneurship Studies, 2024)
This study aims to understand student perceptions regarding entrepreneurship learning in Islamic Higher Education, specifically focusing on the Sharia Economic Law Study Program. Conducted as a survey, this research involves 121 students who responded to an online questionnaire designed to capture personal, cultural, and psychological aspects influencing perceptions. A regression analysis was used to analyze the data, revealing distinct findings across the three aspects. From a personal perspective, students expressed a strong inclination towards entrepreneurship, driven by the growing trend of youth entrepreneurship, which serves as an inspiration and motivation. In terms of cultural influence, students acknowledged the supportive role of their families, particularly noting that their parents grant them the freedom to pursue careers aligned with their interests, including entrepreneurship. Lastly, the psychological dimension highlighted that students perceive entrepreneurship courses as catalysts for generating new ideas, fostering creativity, and enhancing problem-solving skills. These findings underscore the multifaceted impact of entrepreneurship education, suggesting that exposure to entrepreneurship courses shapes students’ aspirations and attitudes toward career development, personal empowerment, and the entrepreneurial mindset. This study provides valuable insights for curriculum developers, emphasizing the need to integrate practical components that reinforce the personal, cultural, and psychological dimensions of entrepreneurship learning.